The Pursuit of Primary Human Goods in Men Desisting From Sexual Offending. (March 2019) - Harris, Danielle Arlanda; Pedneault, Amelie; Willis, Gwenda
The good lives model proposes at least 10 primary human goods that are thought to be common to all individuals which, when secured, contribute to enhanced well-being and life satisfaction. Prosocial attainment of primary human goods is thought to promote desistance from crime. However, individuals convicted of sexual offenses face significant obstacles upon their reentry into the community that likely undermine their ability to obtain such goods. The current study explored the pursuit and attainment of primary human goods in a U.S. sample of men convicted of sexual offenses. We interviewed 42 men released into the community to examine the extent to which they desired and pursued primary human goods. Results highlighted that participants valued many of the human goods outlined in the good lives model, but their means to achieve them were restricted considerably by their correctional status. "Interpersonal relationships" and "life/survival" emerged most frequently during the interviews and were identified as the two most important goods. We discuss the negative impact of recent policies on participants' ability to pursue and attain human goods as well as the value of attending regular treatment in obtaining the goods of "knowledge" and "community." Implications for policy and directions for future research are provided.